DAMPAK KENAIKAN TARIF KENAIKAN PPN TERHADAP INFLASI - Rita Rita; Pudji Astuty (Institut Teknologi dan Bisnis Swadharma, 2023)
The impact of the increase in VAT from 10 % to 11% percent increased the price of goods and services which caused people's purchasing power to decrease. This is because the party subject to VAT is the final level consumer or buyer. However, not all goods and services prices have increased, because there are also types of goods and services that are not subject to VAT. The new VAT rate policy has been regulated in Law (UU) Number 7 of 2022 concerning the Harmonization of Tax Regulations. In 2025 the single VAT rate increase, and will continue to 12%. One of the considerations for implementing the VAT increase policy is the reason is that during the pandemic, state revenues dropped while state spending had to be spent on handling the pandemic. Expanding the tax base is also needed so that the government is able to maintain fiscal discipline with a deficit returning to 3 percent in 2023. This research uses the literature research method with the aim of research to find out the impact of the increase in VAT in 2022 that was implemented in April 2022.Dampak adanya kenaikan PPN dari 10 % menjadi 11 % meningkatnya harga barang dan jasa yang menyebabkan daya beli masyarakat menurun. Hal ini karena pihak yang dikenakan PPN adalah konsumen tingkat akhir atau pembeli. Namun, tidak semua harga barang dan jasa naik, sebab ada juga jenis barang dan jasa yang tidak dikenai PPN. Kebijakan tarif PPN yang baru telah diatur dalam Undang-Undang (UU) Nomor 7 Tahun 2022 tentang Harmonisasi Peraturan Perpajakan. Pada 2025 kenaikan tarif tunggal PPN, dan akan berlanjut menjadi 12 %. Salah satu pertimbangan diberlakukannya kebijakan kenaikan PPN adalah Pasalnya selama pandemi, penerimaan negara anjlok sedangkan belanja negara harus digelontorkan untuk penanganan pandemi. Memperluas basis pajak pun diperlukan agar pemerintah mampu menjaga disiplin fiskal dengan defisit kembali ke 3 persen pada tahun 2023. Penelitian ini menggunakan metode penelititianliteratur research dengan tujuan penelitian ingin mengetahui dampak dari kenaikan PPN ditahun 2022 yang diimplementasikan pada April 2022.